2019
DOI: 10.1016/j.ijpddr.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial activity of terpenylquinones on Leishmania infantum and their effects on Leishmania topoisomerase IB

Abstract: Leishmania is the aethiological agent responsible for the visceral leishmaniasis, a serious parasite-borne disease widely spread all over the World. The emergence of resistant strains makes classical treatments less effective; therefore, new and better drugs are necessary. Naphthoquinones are interesting compounds for which many pharmacological properties have been described, including leishmanicidal activity. This work shows the antileishmanial effect of two series of terpenyl-1,4-naphthoquinones (NQ) and 1,4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Considering the couple avarone/avarol, we can notice that, as observed for the antiplasmodial effects, the reduced form (3) is substantially more potent than the oxidized form 1 on both investigated Leishmania parasites. This has been reported also for several antileishmanial naphthohydroquinones which resulted more active than the corresponding naphthoquinones [43]. Instead, the hydroquinone metabolite 3 and the thiazinoquinone 2 exhibited similar values of IC 50 in the range of low micromolar; however, avarol (3) showed a significantly higher SI (see Table 4).…”
Section: In Vitro Activity On Leishmania Parasitessupporting
confidence: 67%
“…Considering the couple avarone/avarol, we can notice that, as observed for the antiplasmodial effects, the reduced form (3) is substantially more potent than the oxidized form 1 on both investigated Leishmania parasites. This has been reported also for several antileishmanial naphthohydroquinones which resulted more active than the corresponding naphthoquinones [43]. Instead, the hydroquinone metabolite 3 and the thiazinoquinone 2 exhibited similar values of IC 50 in the range of low micromolar; however, avarol (3) showed a significantly higher SI (see Table 4).…”
Section: In Vitro Activity On Leishmania Parasitessupporting
confidence: 67%
“…Parameters for pophyllotoxin, etoposide, podophyllic aldehyde and 4 were assigned using ParamChem [ 50 , 51 ]. The overall procedure was similar to that used in Reference [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…There are many reports on the Frontiers in Pharmacology frontiersin.org 10 antiparasitic activities and mechanisms of action of quinone derivatives. It was suggested that naphthoquinones could inhibit glycolysis (Prati et al, 2015), mitochondrial respiration (Salomão et al, 2013;Bombaça et al, 2018;Mendonca et al, 2018) and topoisomerase IB (Perez-Pertejo et al, 2019) in parasites. In addition, quinone derivatives are known to be inhibitors of cytochrome b in P. falciparum (Lane et al, 2018).…”
Section: Antiprotozoal Activitymentioning
confidence: 99%